Concomitant endometrial and gallbladder metastasis in advanced multiple metastatic invasive lobular carcinoma of the breast: A rare case report. (2015) - Bezpalko, Kseniya; Mohamed, Mohamed A.; Mercer, Leo; McCann, Michael; Elghawy, Karim; Wilson, Kenneth
Highlights: Breast cancer metastasis to the uterus or gallbladder is rare. Metastatic breast carcinoma should be ruled out in females presenting with thrombocytopenia. Invasive lobular carcinoma has a unique pattern of metastasis compared to most other types of breast cancer. High index of suspicion should be maintained in patients with invasive lobular breast carcinoma for unusual patterns of metastasis. Invasive lobular breast carcinoma may metastasize synchronously to the endometrium and gallbladder. Metastatic spread should be considered in the differential diagnosis of patients with invasive lobular breast carcinoma presenting with abnormal vaginal bleeding or acute cholecystitis. Abstract: Introduction: At time of presentation, fewer than 10% of patients have metastatic breast cancer. The most common sites of metastasis in order of frequency are bone, lung, pleura, soft tissue, and liver. Breast cancer metastasis to the uterus or gallbladder is rare and has infrequently been reported in the English literature. Presentation of case: A 47 year old female with a recent history of thrombocytopenia presented with abnormal vaginal bleeding. Pelvic ultrasound revealed multiple uterine fibroids and endometrial curettings revealed cells consistent with lobular carcinoma of the breast. Breast examination revealed edema and induration of the lower half of the right breast. Biopsy of the right breast revealed invasive lobular carcinoma. Bone marrow aspiration obtained at a previous outpatient visit revealed extensive involvement by metastatic breast carcinoma. Shortly after discharge, the patient presented with acute cholecystitis and underwent cholecystectomy. Microscopic examination of the gallbladder revealed metastatic infiltrating lobular carcinoma. The final diagnosis was invasive lobular carcinoma of the right breast with metastasis to the bone marrow, endometrium, gallbladder, regional lymph nodes, and peritoneum. Discussion: The growth pattern of invasive lobular carcinoma of the breast is unique and poses a challenge in diagnosing the cancer at an early stage. Unlike other types of breast cancer, it tends to metastasize more to the peritoneum, ovary, and gastrointestinal tract. Metastasis to the endometrium or gallbladder is rare. Conclusion: Metastatic spread should be considered in the differential diagnosis of patients with invasive lobular breast carcinoma presenting with abnormal vaginal bleeding or acute cholecystitis.